Sleep state misperception: is there a CNS structural source? - Truzzi, Giselle de Martin; Teixeira, Igor de Lima; Prado, Lucila Bizari Fernandes do; Prado, Gilmar Fernandes do; Tufik, Sergio; Coelho, Fernando Morgadinho (Sleep Science, 2021)
Introduction: We describe a case of sleep state misperception in a patient with a neurotoxoplasmosis lesion in the left nucleocapsular region.Case report: A 40-year-old female patient presented relating sleeplessness over the past 2 years, concurrent with progressive headaches, dizziness and motor and sensory deficits in the right upper and lower limbs. She had a history of AIDS, on irregular antiretroviral therapy and neurotoxoplasmosis. A polysomnography confirmed the hypothesis of sleep state misperception, and magnetic resonance imaging revealed a residual lesion in the left nucleocapsular region.Conclusion: Different models consider that the sleep state misperception could be correlated to structural abnormalities of the central nervous system. A recent study showed that the medial prefrontal cortex had a lower activation in patients with unrefreshing sleep due to chronic fatigue syndrome. This case report highlights the possibility of sleep state misperception having - at least partially - an anatomical substrate in the left nucleocapsular region.
Keywords: Sleep; Toxoplasmosis, Cerebral; Sleep Initiation and Maintenance Disorders; Acquired Immunodeficiency Syndrome